Partnerships between intercultural preschools and Mapuche communities in Metropolitan Region, Chile: Negotiations in a contact zone - Becerra Lubies, Rukmini; Mayo González, Simona (Education Policy Analysis Archives, 2017)
The Intercultural and Bilingual Education program in Chile requires intercultural and bilingual preschools to work collaboratively with Mapuche communities to offer a relevant education for Indigenous children; however, no researchers have studied this partnership. In this context, the main objective of this study is to examine the relationships within the communities that have emerged around intercultural and bilingual preschools in Región Metropolitana, Chile. Using the notion of contact zone (Pratt, 1992) we analyze characteristics of the ties developed between members of the preschool institution and the participants of the Mapuche communities. To address this goal, we conducted a qualitative case study, and with ethnographic techniques we collected data using semi-structured interviews, participant observation and group conversations in two preschools; data were codified and categorized with thematic analysis. The main findings show that in this contact zone, the Mapuche communities participate primarily in cultural events, the Educators of Indigenous Language and Culture (ELCIs) are poorly valued and, outside the classrooms these partnerships are seen as learning spaces by the preschool teachers.